2018
DOI: 10.1111/apa.14494
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural dysfunctions of 10‐year‐old children born extremely preterm associated with corticotropin‐releasing hormone expression in the placenta

Abstract: Overall, placenta CRH mRNA concentrations in the top or bottom quartiles were not associated with increased risks of dysfunctions 10 years later. Girls whose placenta CRH expression was in the top quartile, however, were at increased risk of seven indicators/correlates of social limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Meanwhile, Leviton et al. found that girls born EPT who had higher placenta corticotropin‐releasing hormone expression appeared to be at increased risk of social dysfunction at the age of 10 . This issue also contains an editorial by Peter Anderson, which discusses why cognitive outcomes in children born very preterm are not improving (8).…”
Section: Negative Outcomes In Children Born Very or Extremely Pretermmentioning
confidence: 99%
“…Meanwhile, Leviton et al. found that girls born EPT who had higher placenta corticotropin‐releasing hormone expression appeared to be at increased risk of social dysfunction at the age of 10 . This issue also contains an editorial by Peter Anderson, which discusses why cognitive outcomes in children born very preterm are not improving (8).…”
Section: Negative Outcomes In Children Born Very or Extremely Pretermmentioning
confidence: 99%